TRADISI EHA’A DALAM AKTIVITAS PERTANIAN MASYARAKAT KABUPATEN KEPULAUAN TALAUD (Studi Kasus Masyarakat Desa Bambung) - Ulalu, Lucky Winston; Mawara, Jetty E. T.; Deeng, Djefry (Universitas Sam Ratulangi, 2021)
Talaud Islands Regency, the majority as coconut farmers, or commonly known as Copra. In the collo daily language Talaud people pronounce the term Mako'e or copra management process is a form of the result of harvesting coconut fruit. The other work they do is fishermen but thus the Talaud community especially the people of Bambung village work more as coconut farmers (copra). The people of Bambung Village there is a tradition called Eha'a, thi stradition that regulates the people of Bambung village how to harvest coconut plants at a time that has been determined by the Eha'a tradition. There are several things that are the belief of the people of Bambung village, among others; The belief of the Bambung villagers in the tradition of Eha'a towards the people who take other people's coconuts for example, the community was given sanctions in the form of being ordered to shout along the village with shouts such as an apology to the indigenous government and to all residents in the village, as well as other sanctions such as ordered, paying fines that had been agreed by the customary rules. Harvest activities carried out by the People of Bambung Village are based on the principle of life that is closely related to social and spiritual values that contain a very deep meaning, namely about the relationship between human beings, nature (environment), and God.Keywords: Eha'a, coconut farmers, tradition